EDUKASI NUTRISI YANG TEPAT PADA PASIEN YANG MENJALANI KEMOTERAPI DI RSUP WAHIDIN SUDIROHUSODO MAKASSAR - Nurul Fadhilah (Journal of Community Engagement in Nursing, 2024)
Gynecological cancer is a major disease that attacks women. Approximately 94,000 women were diagnosed with gynecologic cancer in 2012 and 2016 (CDC, 2019). Until now, the main therapy in treating cancer disease, including gynecological cancer, is chemotherapy. Even though it is effective in killing cancer cells, chemotherapy has many side effects for sufferers. These effects included nausea, vomiting, diarrhea, and a bitter taste in the mouth. That conditions cause a decrease in appetite and can affect nutritional status in the long term. Proper nutrition is very important in supporting the health of patients undergoing chemotherapy, but there are still many sufferers, especially ordinary people who do not know what proper nutrition is like for patients undergoing chemotherapy. For this reason, the aim of this service is to provide education to patients and families undergoing chemotherapy in the treatment room at Wahidin Sudirohusodo Hospital, Makassar. Education is provided using lecture and discussion methods, using posters and leaflets. The number of participants who took part was 10 people. After being given education, patients know about the importance of nutrition during chemotherapy, foods/drinks that need to be consumed or should be avoided during chemotherapy. Patients and families were enthusiastic during activity.